Snapshots of conformational changes of NtrX receiver domain shed light into its signal transduction mechanism - Fernandez, Ignacio (2015)
Brucella abortus is an important pathogenic bacterium that has to overcome oxygen deficiency in order to achieve a successful infection. Previously, we proved that a two-component system formed by the histidine kinase NtrY and the response regulator NtrX is essential to achieve an adaptive response to low oxygen tension conditions. Even though the relevance of this signaling pathway has already been demonstrated in other microorganisms, its molecular activation mechanism has not yet been described in detail. In this article, we report the first crystal structures from different conformations of the NtrX receiver domain from B. abortus, and we propose a sequence of events to explain the structural rearrangements along the activation process. The analysis of the structures obtained in the presence of the phosphoryl group analog beryllofluoride led us to postulate that changes in the interface formed by the α4 helix and the β5 strand are important for the activation, producing a reorientation of the α5 helix. Also, a biochemical characterization of the NtrX receiver domain enzymatic activities was performed, describing its autophosphorylation and autodephosphorylation kinetics. Finally, the role of H85, an important residue, was addressed by site-directed mutagenesis. Overall, these results provide significant structural basis for understanding the response regulator activation in this bacterial two-component system.